Characterization and antibacterial activity test of chitosan-silver nanoparticle gel and binahong leaf extract (Anredera cordifolia (Tenore) Steen) against Staphylococcus aureus - Indira Dwi Aulia; Sari Edi Cahyaningrum (Jurnal Pijar Mipa, 2023)
Binahong leaf is one of the medical plants that contain alkaloids, saponins, and flavonoids, which directly act as antibiotics. Additionally, chitosan and silver nanoparticles also possess antibacterial properties. This study aims to determine the antibacterial activity of a gel preparation against Staphylococcus aureus bacteria. It was a true experimental study with data collection carried out at the inorganic level. This study's results show that the gel preparation's organoleptic test meets the requirements for skin pH of 4.5-6.5. The spreading test meets the need for good distribution on the skin, which is 5-7cm. The antibacterial activity test showed that the largest diameter of the inhibition zone was observed at concentration F5 (5% binahong leaf extract), which was 13.4 mm.